The role of PML in hematopoietic and leukemic stem cell maintenance - Nakahara, Fumio (2014)
The tumor suppressor promyelocytic leukemia (PML) was first identified as a component of PML–RARα fusion protein, one of the initiating cytogenetic abnormalities in acute promyelocytic leukemia. PML is now known to have diverse functions regulating the DNA-damage response, apoptosis, senescence, and angiogenesis. Recent investigations have identified PML as a regulator of metabolic pathways in stem cell compartments, including the hematopoietic system, and have provided researchers with new strategies for controlling stem cell maintenance and differentiation. Studies of PML in leukemia-initiating cells demonstrate that PML is also an essential component of their maintenance, which has drawn tremendous attention to PML from scientists in various stem cell fields. Here, we review research into PML and its associated pathways, including recent studies of PML as it relates to stem cell biology, as well as our finding that PML regulates fatty acid oxidation, which is essential to the maintenance of normal hematopoietic stem cells. We also discuss the therapeutic potential of controlling PML-associated pathways. In particular, we describe promising evidence for the use of arsenic trioxide in the treatment of chronic myeloid leukemia.